If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 + -6x = -3(x + -7) Reorder the terms: 45 + -6x = -3(-7 + x) 45 + -6x = (-7 * -3 + x * -3) 45 + -6x = (21 + -3x) Solving 45 + -6x = 21 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 45 + -6x + 3x = 21 + -3x + 3x Combine like terms: -6x + 3x = -3x 45 + -3x = 21 + -3x + 3x Combine like terms: -3x + 3x = 0 45 + -3x = 21 + 0 45 + -3x = 21 Add '-45' to each side of the equation. 45 + -45 + -3x = 21 + -45 Combine like terms: 45 + -45 = 0 0 + -3x = 21 + -45 -3x = 21 + -45 Combine like terms: 21 + -45 = -24 -3x = -24 Divide each side by '-3'. x = 8 Simplifying x = 8
| 3x-9=-18-6x | | 2x+3x=-18 | | 11f=3f+18-10f | | (9w+5)4=92 | | 4x^3+13x^2+10x=0 | | 0=3x^2-5x+450 | | 4m-10m=-6 | | -6(x+2)-42=4-16 | | a(a-3)+6-2a=0 | | 5.1+7x=8x+2.3 | | 6x-2-8x=0 | | 8p-3+6p+3=-8(4p+8)+8(-2p+8) | | 0=3x^2-5+450 | | -7+4x+3-x= | | 2(3r+4)=26 | | 16t^2-64t+48=0 | | t^3-8= | | 3n=3n-53 | | .56+4=2(b+2) | | 11x=5x+8 | | 5.5*59=x | | 6x^3-25x^2+24x=0 | | 5-6x=110+9x | | c+34=62 | | 6x^3-25x^2+24=0 | | -3+8(-0.25)= | | 3m+6=15 | | 2m+2+2m=-2 | | 5x-4(x+2)=14 | | 3y-(2-3y)=40 | | 6s^2-5s+1=0 | | 3(x+3)-2=4(x-1) |